2016
DOI: 10.1055/s-0042-109393
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Full µ-Opioid Receptor Agonists is not Impaired by Concomitant Buprenorphine or Mixed Opioid Agonists/Antagonists – Preclinical and Clinical Evidence

Abstract: Buprenorphine and the mixed agonists/antagonists nalbuphine and pentazocine, formerly classified as µ-opioid (MOP) receptor antagonists, have more recently been shown to be partial to full agonists of the human MOP receptor. These receptors do not necessarily have to be maximally activated for a full physiological response. Partial agonists can also sufficiently stimulate signaling processes leading to a full analgesic response, as shown by the effectiveness of buprenorphine, nalbuphine and pentazocine in anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The authors describe overall evidence on analgesic effects of buprenorphine, pentazocine or nalbuphine in co-administration with opioid analgesics, under various clinical pain conditions. They contradict the consensus that these compounds diminish μ-opioid (MOP) receptor analgesia when co-administered with a full MOP receptor agonist and may potentially provoke opioid withdrawal [1].…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The authors describe overall evidence on analgesic effects of buprenorphine, pentazocine or nalbuphine in co-administration with opioid analgesics, under various clinical pain conditions. They contradict the consensus that these compounds diminish μ-opioid (MOP) receptor analgesia when co-administered with a full MOP receptor agonist and may potentially provoke opioid withdrawal [1].…”
mentioning
confidence: 90%
“…We read with great interest the paper by van Niel, J. Schneider and Tzschentke [1] titled "Efficacy of Full μ-Opioid Receptor Agonists is not Impaired by Concomitant Buprenorphine or Mixed Opioid Agonists/Antagonists -Preclinical and Clinical Evidence". The authors describe overall evidence on analgesic effects of buprenorphine, pentazocine or nalbuphine in co-administration with opioid analgesics, under various clinical pain conditions.…”
mentioning
confidence: 99%
“…[50][51][52] There has been no evidence to suggest that butorphanol, nalbuphine, or pentazocine significantly interfere with full mu opioid receptor agonists, but rather, they act synergistically when used at clinically relevant doses. 53,54 It is reasonable to continue these agents preoperatively, as long as one remembers this synergistic response.…”
Section: Butorphanol Nalbuphine and Pentazocinementioning
confidence: 99%
“…Also, randomised studies have shown that comedication with nalbuphine can reduce the incidence of post-operative, morphine-induced pruritus in opioid-naive patients [42,43], including children [44]. Neither reduced efficacy of opioid agonists nor withdrawal symptoms after combination with nalbuphine could be observed in several studies [41,42,[45][46][47]. An additive analgesic effect was even noted in a randomised cohort trial when the drugs were given simultaneously, probably explained by the agonistic and hence additional analgesic effect of nalbuphine on the kappa receptor [45].…”
Section: No Measures Requiredmentioning
confidence: 99%